2001
DOI: 10.1029/2001ja000138
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of diffuse aurora with plasma sheet electrons in pitch angle diffusion less than everywhere strong

Abstract: Abstract. To investigate the spatial and spectral structure of the diffuse aurora during a model geomagnetic storm characterized by random impulses in the cross-magnetospheric convection electric field, we simulate the bounce-averaged drift motion and precipitation of plasma sheet electrons. Bounce-averaged drift trajectories are computed from a Hamiltonian formulation in which we have treated the plasma sheet electrons as though they were undergoing strong pitch angle diffusion in Dungey's model magnetosphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(85 citation statements)
references
References 57 publications
2
82
0
Order By: Relevance
“…We imposed a limiting local flux based on the concept from ionospheric theory (Barakat et al, 1987), and the highest fluxes observed in the Strangeway et al (2005) data set. We also realized that the precipitating electron density is closely related to diffuse auroral luminosity, so we used a prescription from Chen and Schulz (2001) who found evidence that pitch angle diffusion is not generally strong enough to fill the loss cone, and has a local time dependence with a peak in the pre-noon sector, again as summarized in Table 1.…”
Section: Article In Pressmentioning
confidence: 98%
“…We imposed a limiting local flux based on the concept from ionospheric theory (Barakat et al, 1987), and the highest fluxes observed in the Strangeway et al (2005) data set. We also realized that the precipitating electron density is closely related to diffuse auroral luminosity, so we used a prescription from Chen and Schulz (2001) who found evidence that pitch angle diffusion is not generally strong enough to fill the loss cone, and has a local time dependence with a peak in the pre-noon sector, again as summarized in Table 1.…”
Section: Article In Pressmentioning
confidence: 98%
“…The conductance consists of two contributions: (i) Solar-EUV-generated conductance that is estimated from the IRI-90 empirical ionosphere driven by F 10.7 and the Ap index and (ii) auroral conductance, which depends on electron precipitation estimated from the Chen and Schulz [2001] MLT-dependent scattering rate model (for more details on the calculation of auroral conductances see Gkioulidou et al [2012]). The conductance consists of two contributions: (i) Solar-EUV-generated conductance that is estimated from the IRI-90 empirical ionosphere driven by F 10.7 and the Ap index and (ii) auroral conductance, which depends on electron precipitation estimated from the Chen and Schulz [2001] MLT-dependent scattering rate model (for more details on the calculation of auroral conductances see Gkioulidou et al [2012]).…”
Section: Comparision With a Modeled Plasma Sheetmentioning
confidence: 99%
“…These investigations suggest that whistler mode chorus waves may be responsible for the loss of the plasma sheet electrons in the morning sector. The scattered electrons precipitate into the atmosphere, and contribute to diffuse auroral emissions in the morning sector [Thomsen et al, 1998;Chen and Schulz, 2001;Newell et al, 2009].…”
Section: Electron Loss Time Scalementioning
confidence: 99%
“…To obtain the total loss time scales t, we include the effect of the strong diffusion limit, and the expression by Chen and Schulz [2001] is used in the present study. Thus, the electron loss time scale is given as…”
Section: Evaluation Of Theoretical Loss Time Scales Based On Pitch Anmentioning
confidence: 99%